2017
DOI: 10.1039/c7ee01737e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh thermoelectric performance in Cu2Se-based hybrid materials with highly dispersed molecular CNTs

Abstract: By utilizing the interaction between Cu and CNTs, a record-high zT of 2.4 has been achieved in Cu2Se/CNT hybrid materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
230
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 328 publications
(237 citation statements)
references
References 27 publications
6
230
1
Order By: Relevance
“…Both Zhao et al and Liu et al have reported the peak zT value of SnSe can be higher than 2 when the temperature is above 800 K. Meanwhile, most other results suggest the peak zT values of SnSe are at the temperature range lower than 800 K . When the temperature is between ≈800 and ≈1000 K, Cu 2 X, PbX (X = Te, Se, and S), SnTe as well as low‐cost and stable BiCuSeO are more attractive. Through nonequilibrium processing, Tan et al have achieved a record‐high zT value of 2.5 in Pb 0.98 Na 0.02 Te‐8%SrTe at 923 K. As a potential substitution for highly toxic PbTe, peak zT values of SnTe of ≈1.5 have also been widely reported .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Both Zhao et al and Liu et al have reported the peak zT value of SnSe can be higher than 2 when the temperature is above 800 K. Meanwhile, most other results suggest the peak zT values of SnSe are at the temperature range lower than 800 K . When the temperature is between ≈800 and ≈1000 K, Cu 2 X, PbX (X = Te, Se, and S), SnTe as well as low‐cost and stable BiCuSeO are more attractive. Through nonequilibrium processing, Tan et al have achieved a record‐high zT value of 2.5 in Pb 0.98 Na 0.02 Te‐8%SrTe at 923 K. As a potential substitution for highly toxic PbTe, peak zT values of SnTe of ≈1.5 have also been widely reported .…”
Section: Introductionmentioning
confidence: 98%
“…Through nonequilibrium processing, Tan et al have achieved a record‐high zT value of 2.5 in Pb 0.98 Na 0.02 Te‐8%SrTe at 923 K. As a potential substitution for highly toxic PbTe, peak zT values of SnTe of ≈1.5 have also been widely reported . More interestingly, multiple studies demonstrate that the peak zT values of superionic Cu 2 X‐based thermoelectric materials can be higher than 2 in the temperature range from ≈800 to ≈1000 K (mainly Cu 2 Se‐based ones) . Strongly anisotropic and stable BiCuSeO with layered structure has also secured the zT values as high as ≈1 at ≈900 K .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a, Cu 2 Se possesses two sublattices: the rigid FCC framework of Se atoms and the disordered and flowing sublattice of Cu. At high temperatures, Cu ions migrate from one site (interstitial one formed by Se) to another, exhibiting a flowing character that is Figure 1 Timeline of zT for selected Cu-based superionic conductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (red), tetragonal [28][29][30][31][32][33][34][35][36][37] (blue) and distorted [38][39][40][41][42][43][44][45][46][47][48][49] (green) diamond-like materials and BiCuSeO oxyselenides (purple) [50][51][52][53][54][55][56][57][58][59]…”
Section: Decoupled Transport Properties By Two Independent Sublatticesmentioning
confidence: 99%
“…Studies on Cu 2 X liquid-like materials have also been extended to nanostructured composites. By utilizing the special interaction between metal Cu and multi-walled carbon nanotubes (CNTs), Nunna et al [21] realized the in-situ growth of Cu 2 Se on the surface of CNTs and then fabricated a series of Cu 2 Se/CNTs hybrid materials. Due to the high-degree homogeneously dispersed molecular CNTs inside the Cu 2 Se matrix, a zT of 2.4 at 1,000 K has been achieved.…”
Section: Liquid-like or Superionic Materialsmentioning
confidence: 99%